Principles of Economics - N. Gregory Mankiw (Cengage Learning, 2014)
The book provides students with a solid foundation to the principles and concepts of economics. Written for students taking economics for the first time, in focuses on core concepts and how these concepts are appliedto the real world. The word economy comes from the Greek word that refers to "those who manage households." The management or management of resources belonging to these communities is crucial because the resources are limited or scarce. Rarity or scarcity is a situation where people have limited resources and therefore can not provide all the goods and services desired. Scarcity is sometimes relative, depending on the situation and conditions of the communities concerned. In the economy, there are ten principles of economics is divided into three parts. That is how people make decisions, how people interact, and how an economy works as a whole